Electronics fundamentals : circuits, devices, and applications. - Floyd, Thomas L., 1939- (Upper Saddle River : Pearson, 2004)
This renowned book offers a comprehensive yet practical exploration of basic electrical and electronic concepts, hands-on applications, and troubleshooting. Written in a clear and accessible narrative, the Sixth Edition focuses on fundamental principles and their applications to solving real circuit analysis problems, and devotes six chapters to examining electronic devices. With an eye-catching visual program and practical exercises, this book provides readers with the problem-solving experience they need in a style that makes complex material thoroughly understandable. For professionals with a career in electronics, engineering, technical sales, field service, industrial manufacturing, service shop repair, and/or technical writing.